Electrodeposition and Characterization of Cobalt on Copper Electrodes in The Fabrication of Potentiometric Sensors For Phosphate Ion - Siswoyo; Zulfikar; Chintya Maharani; Asnawati; Yeni Maulidah Muflihah; Tri Mulyono (Department of Chemistry, FMIPA, UNEJ, 2025)
Determination of phosphate levels can be done using the potentiometric method with cobalt material-based electrodes with various techniques and compositions. This study uses copper metal as a supporting material. Surface coating of copper was carried out using solution of cobalt chloride and cobalt sulphate in various concentrations by applying voltammetric electrodeposition technique. The electrodes produced for each concentration of cobalt source were examined for the peak-reducing current. The potentiometric response was characterized using a standard phosphate solution, and the morphology using SEM. The best electrodes were used for soil phosphate analysis, and the results were compared with spectrometric methods. The results showed that the optimum concentration of cobalt source solution was characterized by the highest reduction peak of cobalt, namely at a concentration of 0.1 M. Electrodes made with chloride solution produced a higher peak of reduction current, had a sensitivity of -16.21 mV/decade which higher than that of electrodes from sulphate solution, namely -14.59 mV/decade in the phosphate concentration range of 0.001-1000 ppm. The morphology of the two types of electrodes also show differences, the electrode made of chloride material has a surface morphological structure that looks uneven and pretty rough, and there are oval grains that form like crystals and have a uniform shape. In contrast, the electrode made of sulphate material looks flatter and smooth and forms lumps. The results of the analysis of phosphate levels in the soil samples using the electrode are similar to the results of the analysis of the spectrophotometric method